Insidensi dan Keparahan Penyakit Bercak Daun Disebabkan oleh Curvularia sp. pada Pembibitan Kelapa Sawit di Kabupaten Banyuasin Sumatera Selatan - Cameron, Rizky Randal; Febrianni, Astri; Yusticia, Stenia Ruski (Politeknik Negeri Lampung, 2024)
In Indonesia, there has been a notable expansion in the area and productivity of oil palm plantations. Oil palm is among the top seven plantation commodities prioritized for development. High-quality seedlings are essential for optimal plant production. However, several factors can impede oil palm productivity, including diseases that affect oil palm seedlings. One such disease is brown spot disease caused by the fungus Curvularia sp. The objective of this study was to determine the incidence and severity of brown spot disease in oil palm seedlings. The research was conducted from May 2023 to June 2023 in Banyuasin Regency using a purposive sampling survey method. Thirteen seedling locations were selected based on their adherence to good seedling criteria. Seedlings aged 6-12 months were used in this study. At each location, five plots were surveyed, with 30-32 seedlings sampled per plot. Supporting data, including fertilization, watering, and herbicide and fungicide application, were tabulated to supplement the research findings. Results indicated that brown spot disease can affect plants as young as two weeks old. Initial symptoms include brown spots that eventually widen and merge with other spots. The average incidence of the disease was 93.29 % (± 7.89), with an average severity of 47.13% (± 13.23).